2015
DOI: 10.3389/fmicb.2014.00745
|View full text |Cite
|
Sign up to set email alerts
|

A genomic region involved in the formation of adhesin fibers in Bacillus cereus biofilms

Abstract: Bacillus cereus is a bacterial pathogen that is responsible for many recurrent disease outbreaks due to food contamination. Spores and biofilms are considered the most important reservoirs of B. cereus in contaminated fresh vegetables and fruits. Biofilms are bacterial communities that are difficult to eradicate from biotic and abiotic surfaces because of their stable and extremely strong extracellular matrix. These extracellular matrixes contain exopolysaccharides, proteins, extracellular DNA, and other minor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
113
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(121 citation statements)
references
References 58 publications
6
113
2
Order By: Relevance
“…This is very different from the case in B. subtilis, in which the epsA-O operon is essential for biofilm formation under all tested conditions. On the other hand, the results from another recent study demonstrated that protein components made from TasA-and SipW-like proteins in B. cereus seem to play a structural role in matrix assembly (21). However, even with recent progress, current knowledge about the genetics of B. cereus biofilm formation is still largely lacking.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…This is very different from the case in B. subtilis, in which the epsA-O operon is essential for biofilm formation under all tested conditions. On the other hand, the results from another recent study demonstrated that protein components made from TasA-and SipW-like proteins in B. cereus seem to play a structural role in matrix assembly (21). However, even with recent progress, current knowledge about the genetics of B. cereus biofilm formation is still largely lacking.…”
mentioning
confidence: 69%
“…Biofilms formed by various B. cereus strains, as shown in previous studies, although diverse, were in general less robust and demonstrated fewer morphologically distinct features than those in B. subtilis (20,21,24,26). We hoped to develop a robust method to study biofilm formation in B. cereus, similar to what we have in B. subtilis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…difficile , pili have only been shown for cells grown on agar plates [73, 75, 76], suggesting that also for these species the expression of pili depends on the growth conditions. Besides type IV pili, also other types of pili have been found for gram-positive bacteria, including amyloid fibers for Bacillus species [77, 78] and covalently bound pilins for Streptococcus species [79]. Two gene clusters of putative type IV pili biosynthesis genes were identified in the genome of C .…”
Section: Discussionmentioning
confidence: 99%
“…Among the various physiological stages of B. cereus, spores have the greatest biofilm formation potential (Pagedar & Singh, 2012). CalY and TasA, coded by gene calY and operon sipW-tasA, respectively, cooperate to assemble robust and stable fibres with amyloid properties and are important for B. cereus biofilm assembly (Caro-Astorga, P erez-García, de Vicente, & Romero, 2015). Adhesion of B. cereus to stainless steel surface increases with the increase in temperature, pH and time (Peña et al, 2014).…”
Section: Biofilm and Its Hazard In The Dairy Environmentmentioning
confidence: 98%